2017
DOI: 10.1016/j.bbi.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome, immunity, and schizophrenia and bipolar disorder

Abstract: Schizophrenia and bipolar disorder are serious neuropsychiatric disorders of uncertain etiology. Recent studies indicate that immune activation may contribute to the etiopathogenesis of these disorders. Numerous studies in animal models indicate that the mucosal microbiome may influence cognition and behavior by altering the functioning of the immune system. It is thus likely that the microbiome plays a role in human psychiatric disorders. The study of immune alterations and the microbiome in schizophrenia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(138 citation statements)
references
References 61 publications
2
131
1
4
Order By: Relevance
“…Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD . The findings on the reduced risk of psychiatric hospitalizations for patients on antibiotics and non‐steroidal anti‐inflammatory drugs contribute to the evidence suggesting the importance of immune alterations, inflammation, and the microbiome in BDs …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our data, baseline substance use disorder, psychosis, and use of anticonvulsants and anxiolytics were previously reported to be risk factors for hospitalization in BD . The findings on the reduced risk of psychiatric hospitalizations for patients on antibiotics and non‐steroidal anti‐inflammatory drugs contribute to the evidence suggesting the importance of immune alterations, inflammation, and the microbiome in BDs …”
Section: Discussionsupporting
confidence: 92%
“…30 The findings on the reduced risk of psychiatric hospitalizations for patients on antibiotics and non-steroidal anti-inflammatory drugs contribute to the evidence suggesting the importance of immune alterations, inflammation, and the microbiome in BDs. 34 It is important to consider some additional limitations of the study, This finding can explain why AD monotherapy was the most commonly used treatment regimen and is of particular interest given the concerns about AD-induced risk of manic switch, 35 and potential contribution of the latter to treatment non-adherence. This highlights the challenges of the proper identification of BD in routine care settings and the negative sequelae of an incorrect diagnosis,…”
Section: × 10 −12mentioning
confidence: 99%
“…The principle of probiotic therapy is based on the fact that systemic inflammation is dependent to some extent on gastrointestinal inflammation and the composition of the bacterial flora of the gastrointestinal tract. Furthermore, the composition of the microbiome can modulate inflammation within the central nervous system through a series of interconnections which have been termed the gut‐brain axis . Previous studies have indicated that individuals whose intestinal tract contains potentially pathogenic anaerobic bacteria such as Bacteriodes fragilis and aerobic bacteria such as Escherichia coli are more likely to develop aberrant immune responses than individuals whose intestinal tract consists largely of non‐pathogenic anaerobic bacteria such as lactic acid‐producing bacteria ( Lactobacilli ) and non‐motile Gram‐positive bacteria such as Bifidobacteria .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, similar administration of a combination of L. rhamnosus and B. animalis in patients diagnosed with schizophrenia saw no difference in the psychiatric symptom severity between the placebo and probiotics groups. 311 Contradictory results have emerged from depressed patients who consumed probiotics; while in some studies the use of probiotics seemed not to be associated with lower rates of depression, 318 in other studies the probiotic treatment produced a reduction in network-level neural reactivity to negative emotions, anxiolytic activity, suppression of psychological stress, and reduction of the negative thoughts associated with low mood. 343 …”
Section: Neurodegenerationmentioning
confidence: 99%